2012
DOI: 10.1111/j.1551-6709.2012.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Factors in Conceptual Congruency

Abstract: Conceptual congruency effects are biases induced by an irrelevant conceptual dimension of a task (e.g., location in vertical space) on the processing of another, relevant dimension (e.g., judging words' emotional evaluation). Such effects are a central empirical pillar for recent views about how the mind ⁄ brain represents concepts. In the present paper, we show how attentional cueing (both exogenous and endogenous) to each conceptual dimension succeeds in modifying both the manifestation and the symmetry of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 91 publications
8
72
3
Order By: Relevance
“…Results consistent with the 'up = good' metaphor have also been observed with sentences (Marmolejo-Ramos, Montoro, Elosúa, Contreras & Jiménez-Jiménez, 2014), pictures and faces (Crawford, Margolies, Drake & Murphy, 2006), and even auditory tones (Weger, Meier, Robinson & Inhoff, 2007). They also occur in a variety of different tasks, including online processing tasks (Meier & Robinson, 2004;Santiago, Ouellet, Román & Valenzuela, 2012), memory tasks (Brunyé, Gardony, Mahoney & Taylor, 2012;Casasanto & Dijkstra, 2010;Crawford et al, 2006), and tasks requiring vertical movements (Casasanto & Dijkstra, 2010;Dudschig, de la Vega & Kaup, 2014;Freddi, Cretenet & Dru, 2013;Koch, Glawe & Holt, 2011). People from different ages and cultures show this mapping, which led Tversky, Kugelmass and Winter (1991) to suggest that it is a universal character.…”
Section: Introductionmentioning
confidence: 59%
“…Results consistent with the 'up = good' metaphor have also been observed with sentences (Marmolejo-Ramos, Montoro, Elosúa, Contreras & Jiménez-Jiménez, 2014), pictures and faces (Crawford, Margolies, Drake & Murphy, 2006), and even auditory tones (Weger, Meier, Robinson & Inhoff, 2007). They also occur in a variety of different tasks, including online processing tasks (Meier & Robinson, 2004;Santiago, Ouellet, Román & Valenzuela, 2012), memory tasks (Brunyé, Gardony, Mahoney & Taylor, 2012;Casasanto & Dijkstra, 2010;Crawford et al, 2006), and tasks requiring vertical movements (Casasanto & Dijkstra, 2010;Dudschig, de la Vega & Kaup, 2014;Freddi, Cretenet & Dru, 2013;Koch, Glawe & Holt, 2011). People from different ages and cultures show this mapping, which led Tversky, Kugelmass and Winter (1991) to suggest that it is a universal character.…”
Section: Introductionmentioning
confidence: 59%
“…Here, an upper presentation location speeds up positive valence judgments and a lower presentation location speeds up negative valence judgments (Meier and Robinson 2004). Santiago et al (2012) employed several attentional cueing manipulations and showed that the occurrence of the spatial-valence congruency effect depends on these attentional factors. Specifically, when attention was oriented toward either the word location or the valence of the words, a congruency effect emerged.…”
Section: Discussionmentioning
confidence: 94%
“…Further support for an influence of mediating factors on conceptual interactions comes from a study investigating the spatial-valence congruency effect by Santiago et al (2012). The spatial-valence congruency effect arises when affective valence words are presented in vertical space.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps because creating mental models is intrinsically effortful, mental models are constrained to be as internally coherent and simple as possible, given the requirements of the task at hand. We have proposed elsewhere that this characteristic of mental models is central to accounting for the flexibility of conceptual congruency effects in a wide variety of tasks (Santiago, Ouellet, Román, & Valenzuela, 2012;Santiago et al, 2011). If we assume that both the spatial representation of the input sentence and the mental model of its contents are parts of a superordinate mental model of the whole situation, both entities will tend to unfold in the same direction, because this will increase the internal coherence of the superordinate model.…”
Section: Discussionmentioning
confidence: 99%